2020
DOI: 10.3390/agronomy10101565
|View full text |Cite
|
Sign up to set email alerts
|

Deacclimation of Winter Oilseed Rape—Insight into Physiological Changes

Abstract: Climate changes, which result in the occurrence of periods with relatively high temperatures during the winter, can lead to the deacclimation of cold-hardened plants and cause problems with their winter survival. The aim of these studies was to investigate the physiological changes (photosynthesis and water relations including aquaporin expression) that accompany deacclimation process in the economically important winter oilseed rape plants. The effect of deacclimation on frost tolerance was also estimated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 90 publications
7
38
1
Order By: Relevance
“…A detailed insight into the chemical composition (qualitative) changes caused in the endosperm of maize and barnyard grass seedlings under S, and PNs treatments were tested by the FT-Raman spectroscopy, which allows the characterization of the chemical composition of the tested material. It is a non-destructive method to study the effects of biotic and abiotic stresses on plants [ 48 , 49 ], so it can be successfully used for studies on living plant tissues [ 50 , 51 , 52 ]. After seed imbibition, catabolic processes start germination.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed insight into the chemical composition (qualitative) changes caused in the endosperm of maize and barnyard grass seedlings under S, and PNs treatments were tested by the FT-Raman spectroscopy, which allows the characterization of the chemical composition of the tested material. It is a non-destructive method to study the effects of biotic and abiotic stresses on plants [ 48 , 49 ], so it can be successfully used for studies on living plant tissues [ 50 , 51 , 52 ]. After seed imbibition, catabolic processes start germination.…”
Section: Discussionmentioning
confidence: 99%
“…The conditions used for cold acclimation and de-acclimation in previous studies are not entirely relevant to the field conditions under which cereals are grown. Studies of other plant species, including grasses, also have employed a broad range of approaches to de-acclimation treatments [ 6 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. De-acclimation conditions applied in previous studies often more closely resemble spring warming than mid-winter warm spell, using equal night and day lengths or longer days/shorter nights sometimes accompanied by relatively high temperatures [ 6 , 25 , 28 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the gene annotation performed in the present study also revealed a large number of DEGs involved in photosynthesis or associated with chloroplasts, a distinct overrepresentation of genes encoding oxidoreductases, especially peroxidases, was noted, which the GO analysis did not reveal. It was previously suggested that redox enzymes might play a crucial role in the de-acclimation response [ 4 , 27 ], thus associating the susceptibility to freezing after a warm period, with reduced tolerance to oxidative stress. This suggestion would imply the downregulation rather than upregulation of genes encoding antioxidant enzymes, but the results from the present DEG analysis revealed the upregulation of all genes from this group ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hardening effects of cold temperatures can be reversed in some circumstances by exposing winter plants to higher temperatures, i.e., 15 °C (the so-called deacclimation phenomenon). In natural field conditions, deacclimation is particularly dangerous for winter crops in the winter because it lowers their tolerance to frost [ 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%